Approximation of Two Systems of Radical Functional Equations Related to Quadratic and Quartic Mappings - Ghaziyah Alsahli; Abasalt Bodaghi (Mathematics)
In this work, we define the multi-radical quadratic and multi-radical quartic mappings as two systems of radical functional equations and then represent them as two equations. Then, we establish some results concerning the stability of multi-radical quadratic and multi-radical quartic mappings by applying a fixed-point based on Brzdȩk. As a direct consequence, we prove the Rassias and Hyers stability of the mentioned mappings.